Study of Bacterial L-asparaginase and Molecular expression of l-asparaginase gene in Escherichia coli - Mannaa Ibrahim, Luay (International Journal of Psychosocial Rehabilitation, 2024)
E. coli remains highly active even after it is removed from the blood, possibly bysequestration by liver cells) the half-life of the enzyme is increased when lymphoma cellsare implanted in guinea pigs. Since then, several microorganisms were evaluated toobtain an L-asparaginase with greater antitumor activity compared to that produced by E.coli and that was produced in an economically viable way. It is considered that the newL-asparaginases to be used as medication must have pharmacological activity causingminimal side effects. Thus, it is expected that they present a high affinity for thesubstrate, a half-life time sufficient to avoid administration of several doses, lowimmunogenicity and high stability. It was also postulated that a low cross-glutaminolyticactivity is important to avoid excessive side effects of the enzyme treatment. Variousinformation can be extracted from the simulation trajectory, such as the energy ofinteraction between residues from the catalytic site of an enzyme and its substrate(intermolecular) or interactions that one or more generated mutations may have withneighboring residues within the protein (intramolecular) .In the Total Potential Energyequation, we can see that the first three terms refer to: the bond length, the anglesbetween the atoms and the bond twist, respectively. The fourth term of the equation refersto the calculation for non-directly bonded atoms and for atoms whose interaction isintermolecular, thus considering the van der Waals and Coulomb interactions